2018
DOI: 10.1016/j.ejmech.2018.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Phenylthiazoles with tert-Butyl side chain: Metabolically stable with anti-biofilm activity

Abstract: A new series of phenylthiazoles with t-butyl lipophilic component was synthesized and their antibacterial activity against a panel of multidrug-resistant bacterial pathogens was evaluated. Five compounds demonstrated promising antibacterial activity against methicillin-resistant staphylococcal strains and several vancomycin-resistant staphylococcal and enterococcal species. Additionally, three derivatives 19, 23 and 26 exhibited rapid bactericidal activity, and remarkable ability to disrupt mature biofilm prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Kotb et al [12] designed and synthesized a series of 2,4disubstituted pyrimidines bearing phenylthiazole, among which, compounds 6 and 7 (Figure 2) displayed the MIC values of less than 0.8 μg mL À 1 against methicillin-resistant S. aureus (MRSA), comparable with standard reference vancomycin with an MIC value of 1.56 μg mL À 1 . It was also found that the t-butyl lipophilic group on the benzene ring provided a long half-life time, and the nitrogen side chain at the position 2 of pyrimidine was helpful for anti-enterococcal activity.…”
Section: Monopyrimidine Disubstituted Derivativesmentioning
confidence: 99%
“…Kotb et al [12] designed and synthesized a series of 2,4disubstituted pyrimidines bearing phenylthiazole, among which, compounds 6 and 7 (Figure 2) displayed the MIC values of less than 0.8 μg mL À 1 against methicillin-resistant S. aureus (MRSA), comparable with standard reference vancomycin with an MIC value of 1.56 μg mL À 1 . It was also found that the t-butyl lipophilic group on the benzene ring provided a long half-life time, and the nitrogen side chain at the position 2 of pyrimidine was helpful for anti-enterococcal activity.…”
Section: Monopyrimidine Disubstituted Derivativesmentioning
confidence: 99%
“…109,110 This criteria is clinically important, as it would affect the size of the dosing regimen necessary for patients. 111,112 Through the more than 400 published phenylthiazole derivatives, 110,[113][114][115][116][117][118][119][120][121][122][123][124][125][126] the SAR of this class of compounds has become well dened (Fig. 4).…”
Section: Phenylthiazoles As a Novel Class Of Dual Uppp Andmentioning
confidence: 99%
“…113 Later on, a detailed metabolite analysis was completed and this indicated the presence of an additional metabolic so spot at the butyl benzylic carbon. 125 Addressing this limitation, replacing the methylene so spot with oxygen 125 or acetylenyl 114 moieties or undergoing replacement with t-butyl, 117 has yielded phenylthiazoles with even more pronounced stability with respect to the hepatic metabolism ( Fig. 6).…”
Section: Phenylthiazoles As a Novel Class Of Dual Uppp Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity assessment of aryl isonitrile analogues against human keratinocytes -Compounds 7, 18, and 19 were assayed (at concentrations of 16,32,64, and 128 µM) against a human keratinocyte (HaCaT) cell line (AddexBio, San Diego, CA, USA) to determine the potential toxic effect to mammalian skin cells in vitro, as previously described. [44][45][46][47][48] In brief, cells were cultured in DMEM supplemented with 10% FBS at 37 °C with CO 2 (5%). Control cells received DMSO alone at a concentration equal to that in drug-treated cell samples.…”
Section: Evaluation Of Antibacterial Activity Of Compounds and Contromentioning
confidence: 99%